Upaya Meningkatkan Konsentrasi Belajar PAI Dengan Model PBL di SDN 05 Tarung-Tarung Utara - Suryani, Irma (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the concentration of learning for fifth-grade students in the subject of Islamic Religious Education (PAI) at SDN 05 Tarung-Tarung Utara by implementing the Problem-Based Learning (PBL) model. Based on the problem identification, it was found that low student concentration was caused by the use of monotonous lecture methods without engaging learning media relevant to student interests. Additionally, the lack of active student involvement in the learning process was also a contributing factor. This research uses the Classroom Action Research (CAR) method, consisting of planning, implementation, observation, and reflection cycles. The results of this study are expected to contribute to improving student concentration and focus in learning, as well as creating a more interactive and engaging learning environment for students.